Legal Protection for Retail Investors in Crypto Assets and Digital Tokens: Aligning Regulatory Authority and the Need for Legal Certainty in Indonesia - Jenny Ramadhani Daely; Andreansyah Putra Nasution (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The rapid growth of crypto assets in Indonesia has led to a significant increase in retail investors, yet it has not been adequately accompanied by a regulatory framework capable of providing optimal legal protection. This study aims to analyze the legal framework for retail investor protection in crypto asset transactions, identify regulatory gaps, and examine the implications of the transfer of supervisory authority to the Financial Services Authority. The research employs a normative juridical method with statutory and conceptual approaches, using qualitative analysis of primary, secondary, and tertiary legal materials. The findings indicate that retail investor protection still faces several weaknesses, particularly in terms of information disclosure, protection of client funds, dispute resolution mechanisms, and prevention of manipulative practices. In addition, structural challenges persist, including regulatory gaps during the transition period, the cross-border nature of transactions, and limitations in supervisory capacity. This study highlights the need for adaptive and integrated regulatory strengthening to enhance legal certainty and investor protection within Indonesia’s crypto asset ecosystem.